The impact of advanced age‐related macular degeneration on the National Eye Institute's Visual Function Questionnaire‐25. Issue 7 (30th December 2020) - Patnaik, Jennifer L.; Lynch, Anne M.; Pecen, Paula E.; Jasso, Maria; Hanson, Kara; Mathias, Marc T.; Palestine, Alan G.; Mandava, Naresh
Abstract: Purpose: To assess visual function among patients diagnosed with age‐related macular degeneration (AMD) by stage of disease and laterality. Methods: This is a cross‐sectional cohort study of 739 AMD patients and their responses to the National Eye Institute Visual Function Questionnaire‐25 (NEI VFQ‐25) at time of study enrolment. Patients with AMD were categorized into Early/Intermediate AMD and three groups of advanced AMD: (i) neovascular AMD (NV), (ii) geographic atrophy (GA) and (iii) Both Advanced forms. These three advanced stages were further stratified into unilateral or bilateral advanced disease. Mean composite scores and subscale scores for 12 different areas were based on a 100‐point scale with the lowest and highest possible scores set at 0 and 100, respectively. Scores for the advanced AMD groups were compared with Early/Intermediate AMD using general linear modelling. Results: A total of 739 AMD patients (294 Early/Intermediate, 115 GA, 168 NVAMD and 162 Both Advanced) were included in the analysis. Mean composite scores were highest among Early/Intermediate patients (89.9), followed by patients diagnosed with unilateral disease in the Both Advanced (88.0) and NV (86.1) groups. Mean composite scores were similar for bilateral NV (82.9) and unilateral GA (81.7), and mean scores were lowest for the bilateral GA (71.3) and bilateral Both Advanced (68.5) groups. In general, this pattern persisted across the twelve subscales as well. Subscale scores ranged from a low of 35.1 for driving among bilateral Both Advanced patients to a high of 99.2 for colour vision among patients with unilateral Both Advanced. Overall, patients with unilateral advanced disease consistently had higher mean scores than their bilateral counterparts. The largest difference was 19.5 composite score points between the unilateral and bilateral Both Advanced groups, there was a difference of 10.4 points between the GA groups, and a relatively small difference of 3.2 points between the NV groups. Conclusions: We found large differences in visual function as reported from the VFQ‐25 across the different types of advanced stage AMD groups and number of eyes affected with advanced AMD. These findings demonstrate the importance of accounting for the type and number of eyes affected by advanced stage AMD.